AN EXPERIENCE ON THE DISASTER VICTIM IDENTIFICATION (DVI) FOR INDONESIA AIRASIA FLIGHT QZ8501 (Journal of Forensic Medicine & Toxicology, 2017)
This paper is about sharing of experience of managing air disaster where 162 people died by Indonesian, Malaysian, and International DVI teams. Human remains of 115 deceased were recovered from sea and 111 were successfully identified by multiple means.
Keywords: DVI; air disaster; team approach in DVI